Influence of the birth year of arrival at elite handball male in junior and U18 - Gutierrez Aguilar, O.; Contreras Marin, J.; Saaverda Garcia, M.; Fernandez Romero, J. J.; Acsinte, A.; Hernandez, M.; Vazquez Garrido, I. (EHF Scientific Conference 18.-19.11.2011, Wien, Österreich, 2011)
The handball world championships, organized by the International Handball Federation (IHF), for Juniors and U18´s category, establishes the groups of contesters, on the adscription of athletes born during two consecutive years in the same category, starting with those born in even-numbered year, and must stay two consecutive years in the same category. The sample is composed by 686 handball players, which have played the World Championship of their category on 2009. The recorded variables were the birth year. The differences between the proportion of players born in even-numbered year than the ones which were born in odd year, was calculated by the binomial test, contrasting the proportion of 50%. In Junior and U 18´s category they have been found much more players born in even-numbered years than in odd years, which very big significant differences.